Improved-Efficiency Irradiation Facility for Poultry Farming - Yu. Kovalenko, O; A. Pilshchikova, Yu. (International Journal of Engineering and Technology, 2018)
This article discusses the effectiveness of influence of irradiation lighting facility on the productivity and homogeneity of broilers. Irradiation lighting facility of increased efficiency is proposed. Its spectral composition of radiation sources corresponds to the function of relative spectral sensitivity of the organ of vision, and to the functions of relative spectral erythemal and bactericidal efficiency. The results of experiment in the influence of optical radiation, received from irradiation lighting facility, on an industrial herd of broilers are given in the article.Â Â